Conceptualization of the Dimensions of Environmental Quality in Rural Planning by Participation of Local People and Experts; a Case Study of Shahriar Village, Lordegan County, Iran - kazem rostami; Mehdi Pourtaheri; Abdolreza Roknaldin Eftekhari (تحقيقات جغرافيايی, 2019)
Aims & Backgrounds: with the start of planning in the new form in rural areas, a conflict was created between the demands of villagers from below with the view of planners from the above.  The lack of normative view and pay a little attention to the environmental quality of development have an important role in the expansion of the conflict. The aim of the study was to the conceptualization of environmental quality dimensions in rural planning by the participation of local people and experts. Methodology: In this qualitative study, Sharyar village was selected from the Lordegan county to attract the participation of people in the process of conceptualizing the environmental quality dimensions and optimal planning. The main reason for selecting the Shahryar village as a case study in this research was executing various plans or implementation of many projects in the form of rural planning. 36 aware people, local managers and experts of the shahryar village were organized in the 6 workshops and expectations of the subjects from the concepts of environmental quality in rural planning were determined in the various items. Findings: 202 of the items of environmental quality concepts were collected and the items were ranked by the workgroups in the framework of 5 dimensions, 1 domain, and 44 indexes. 48 items in the form of 9 indicators in physical dimension, 46 items in the form of 10 indicators in social-cultural dimension, 42 items in the form of 8 indicators in economical dimension, 35 items in the form of 8 indicators in the environmental dimension, and 10 items in the form of 3 indicators in the political-administrative dimension were arranged. Conclusion: The five dimensions in the strategic territory template with 21 items and 6 indexes including the capacity, perceived justice, considering the planning, tourist attraction, and dynamism and prioritizing the countrychr('39')s planning system are proposed for evaluating the quality of the rural environment.